COVID-19 en Latinoamérica: Diferencias respecto a las economías desarrolladas - Eduardo Levy Yeyati; Rodrigo Valdés (Revue Internationale de Politique de Développement)
Most analyses of the socioeconomic impact of COVID-19 rely on data from advanced and East Asian economies, for good reasons: those countries were hit first by the pandemic. This debate contrasts with the realities in Latin American countries, not only because of economic restrictions but also because the pandemic dynamics have been surprisingly difficult to control in several countries. Countries that shied away from severe lockdowns are topping daily case rankings, but others that adopted lengthy and stringent measures early on still have a growing number of cases. In this chapter, we discuss how the combination of a limited fiscal and financial space and a precarious labour market, against the backdrop of a delicate political landscape, poses severe challenges to the intensity and the socioeconomic management of the policy response to the pandemic in the region.